PENGARUH MINYAK ATSIRI SERAI (Andropogon citratus DC.) TERHADAP BAKTERI YANG DIISOLASIDARISAPI MASTITIS SUBKLINIS - Masniari Poeloengan (Research Center for Biology-Indonesian Institute of Sciences, 2009)
This study was done to determine the antibacterial properties of water extract and volatile oil of lemon grass (Andropogon citratus DC).Bacteria isolates used in this study were obtained from subclinical mastitis ridden cows and had been identified as Staphylococcus aureus, S. epidermidis, Streptococcus agalactiae and E. coli. The concentrations of water extract and volatile oil used for the test were %, 25%, 12,5% and 6,25%. The antibacterial used was done by paperdisk diffusion method on Mueller Hinton Agar (MHA). The result showed that water extract did not have any antibacterial effect to 4 bacteria isolates., while volatile oil of lemon grass did inhibit the growth of 4 bacteria isolates.Increasing concentration of volatile oil resulted in increasing zone of bacteria growth inhibition.